Penerapan Pelatihan Scratch untuk Meningkatkan Literasi Digital pada Siswa Sekolah Dasar melalui Pembelajaran Pemrograman Visual - Muhammad Syaifur Rohman; Galuh Wilujeng Saraswati; Nurul Anisa Sri Winarsih; Filmada Ocky Saputra; Danny Oka Ratmana; Adhitya Nugraha (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of technology has made it increasingly important for the younger generation to acquire digital literacy skills at an early age. As technology becomes an integral part of daily life, it is essential to introduce fundamental programming concepts to students to prepare them for the future. This community service program aims to introduce 5th-grade students at Elementary School Emmaus Kediri to basic programming concepts using the Scratch platform. The program adopted the Project-Based Learning (PjBL) method, which emphasizes interactive learning through hands-on activities. The one-day session involved 17 students, who underwent a structured process consisting of a pre-test, material delivery, hands-on practice of creating simple animations, and a post-test. The learning materials included an introduction to the Scratch interface, how to use sprites, and basic coding blocks to develop simple animation projects. The evaluation results indicated a significant increase in students' understanding of basic programming concepts. The majority of participants successfully created simple animation projects using coding blocks and sprites, demonstrating their ability to apply the learned concepts. The students showed high enthusiasm throughout the learning process, indicating a strong interest in digital learning and coding. The high level of engagement further supports the potential for expanding similar programs in the future. This community service activity proved effective in introducing computational thinking and fostering creativity among elementary school students. It also demonstrated the effectiveness of interactive and hands-on learning approaches in enhancing students' digital literacy. As a result, this program has the potential to be implemented in other schools to promote early exposure to programming and support the development of digital skills among young learners